PENILAIAN KINERJA BERBASIS BALANCE SCORECARD PADA PERUSAHAAN - Fauzi, Feri; Kanivia, Aan; Dewi, Isti Riana; Aeni, Nurul; Hendrawan, Michael (Fakultas Ekonomi dan Bisnis, 2025)
This study examines the application of the Balance Scorecard as a performance assessment method. In general, performance appraisal often focuses only on the company's financial information. By utilizing the Balanced Scorecard, organizations can be more effective in conveying their business strategy and setting goals to realize the vision and mission that will create strategic progress and improvement to achieve optimal performance of an organization. This study aims to analyze performance evaluation using the Balanced Scorecard approach in an organization. This study applies the literature review method as a research approach. The results of this study show that organizations that apply the Balanced Scorecard and conduct analysis involve four aspects. That way, the organization can monitor progress in achieving competitive advantage, as well as being able to realize the vision-mission and strategy that has been determined through a more structured performanceassessment. Key words: Balanced scorecard, Performance assessment, Business strategy